Sustainable food production - Christou, Paul (Springer, 2013)
Population growth in the coming decades will put severe pressure on human food, animal feed, and fiber production from both land and ocean ecosystems. Environmental sustainability and social justice are increasingly important elements in debates on how to ensure adequate food for a growing global population. Gathering approximately 90 peer-reviewed entries from the Encyclopedia of Sustainability Science and Technology, Sustainable Food Production provides comprehensive coverage of this vital area of current research. Sections on animal breeding and genetics for food, crop science and technology, ocean farming and sustainable aquaculture science and technology, and transgenic livestock for food discuss state-of-the-art scientific advances, and place them in their proper scientific, environmental, ethical, socio-economic, and political contexts